Essays on banking in Africa - (:unkn) unknown (My University, 2018)
This dissertation studies African financial systems with a focus on bank ownership. Chapter one studies cost efficiency. Foreign banks are more efficient than domestic banks, and Pan-African banks are the most efficient banks on the continent. Chapter two analyses lending procyclicality. Lending growth of African banks is sensitive to the GDP per capita growth. Pan-African banks have a less pro-cyclical lending behaviour. Lending growth of African foreign banks is sensitive to GDP per capita growth in their home country. Chapter three and four study financial inclusion. Being male, wealthier, more educated and older to a certain extent increases the likelihood to be financially included. Pan-African banks presence increases firms’ access to credit. Pan-African banks would also increase households’ financial inclusion, but such result is less robust.The general conclusion of this dissertation underlines the new, beneficial role Pan-African banks play on the continent. These young financial institutions increase cost efficiency, reduce cyclicality of lending and improve financial inclusion.
Keywords: African Research